Analisis Kesejahteraan Ekonomi Masyarakat Pesisir dalam Perspektif Maqashid Syariah: Studi Kasus Pantai Gading, Mataram - Muh. Zaini; Evrita Putri Azzahroh; Eny Widiaty (Pustaka Peradaban, 2025)
Enhancing welfare constitutes a strategic resolution to elevate the living standards of fishermen and coastal communities. This research analyzes the welfare level of coastal communities in the Gading Beach Area, Mataram, through the perspective of maqashid syariah as propounded by Imam As-Syatibi and Yusuf al-Qardhawi, and correlates it with the concept of falah in Islamic economics. The research method employed is descriptive qualitative, utilizing data collection techniques such as participatory observation, in-depth interviews, and document analysis. The research findings indicate that the community has fulfilled the five primary indicators of maqashid syariah according to As-Syatibi, namely hifz ad-din (preservation of religion), hifz al-aql (preservation of intellect), hifz al-nafs (preservation of life), hifz an-nasl (preservation of progeny), and hifz al-mal (preservation of wealth). However, an additional indicator proposed by Yusuf al-Qardhawi, hifz al-bi’ah (preservation of the environment), has not been optimally achieved due to coastal ecosystem degradation. This finding confirms that the welfare of coastal communities is not solely contingent upon the fulfillment of basic needs (maslahah), but also on environmental sustainability as an integral component of holistic welfare or falah. The research implications underscore the importance of integrating ecological principles into coastal development policies to ensure economic prosperity and the sustainable maintenance of spiritual values. Peningkatan kesejahteraan merupakan solusi strategis untuk mengangkat taraf hidup nelayan dan masyarakat pesisir. Penelitian ini menganalisis tingkat kesejahteraan masyarakat pesisir Kawasan Pantai Gading, Mataram, melalui perspektif maqashid syariah yang dikemukakan oleh Imam As-Syatibi dan Yusuf al-Qardhawi, serta mengaitkannya dengan konsep falah dalam ekonomi Islam. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan teknik pengumpulan data melalui observasi partisipatif, wawancara mendalam, dan analisis dokumen. Hasil penelitian menunjukkan bahwa masyarakat telah memenuhi lima indikator utama maqashid syariah menurut As-Syatibi, yaitu hifz ad-din (terpeliharanya agama), hifz al-aql (terpeliharanya akal), hifz al-nafs (terpeliharanya jiwa), hifz an-nasl (terpeliharanya keturunan), dan hifz al-mal (terpeliharanya harta). Namun, indikator tambahan yang dikemukakan oleh Yusuf al-Qardhawi, yakni hifz al-bi’ah (terjaganya lingkungan), belum tercapai secara optimal akibat degradasi ekosistem pesisir. Temuan ini mengonfirmasi bahwa kesejahteraan masyarakat pesisir tidak hanya bergantung pada pemenuhan kebutuhan dasar (maslahah), melainkan juga pada keberlanjutan lingkungan sebagai bagian integral dari kesejahteraan holistik atau falah. Implikasi penelitian menekankan pentingnya integrasi prinsip-prinsip ekologis ke dalam kebijakan pembangunan pesisir guna menjamin kemakmuran ekonomi dan pemeliharaan nilai-nilai spiritual secara berkelanjutan.